Study the Potential Role of Nutritional Properties and Fertility for Some Cereals and Nuts in Experimental Male Albino Rats Poisoned with Nicotine - Abdulmaguid, Nabila Mahmoud (Journal of natural sciences, life and applied sciences, 2018)
Over the years, male fertility has been on the decline with environmental and congenital factors. This study investigated the nutritional effect of barley, oat, walnuts, almonds, hazelnuts and peanuts on biological evaluation, semen analysis, fertility hormones and histopathological examination of testis. Forty eight mature male rats feed on diet mixed with cereals (barley and oat 10%) and nuts (walnuts, almonds, hazelnuts and peanuts 2.5%) of each one for group after 30 days nicotine injection. The results showed significant decrease of body weight, feed efficiency ratio, relative organs weight, motility %, progressive %, sperms count and histopathological changes of testis as a results of nicotine injection. But, the supplemented diet with cereals and nuts ameliorated the previous data toward the normal level comparing nicotinic group. So, these results confirmed that cereals and nut supplements can be used to improve infertility against nicotine toxicity among male rats’ hens, smokers due to high nicotine intake.